La Musicalidad Como Estrategia De Bienestar Y Conectividad Del Intersticio Urbano (Zona Centro Fundacional De Ibagué) (2022)
The present degree work analyzes and generates an urban connection on the existing musical urban elements in the central (foundational) area of Ibagué-Tolima, taking as the main factor the wellbeing of its residents and passers-by; presenting in a particular way in terms of joints, taking as a primary factor the mobility of people and for people, generating spaces for permanence and continuous walking flowing over the cultural beauties found in this place, in tours of a maximum of 15 minutes . All this seeking to strengthen the musical aspects, giving them the importance and hierarchy they deserve, providing a clearer perspective and focus of the musical city of Colombia, starting from its essence (downtown).